Pengembangan Objek Wisata Sawah Sumber Gempong Oleh Badan Usaha Milik Desa - Chelvi Okvian Suwardi; Tukiman Tukiman (Universitas Musamus, Merauke, Papua, 2023)
Sumber Gempong Rice Field Tourism is a tourist destination that has great natural potential and is located in Ketapanrame Village, Trawas District, Mojokerto Regency. In the development, management and development of tourism is carried out jointly as managers and investors. Even though it was only inaugurated in December 2021, this tour is capable of becoming the largest producer of the Mutiara Welirang Village-Owned Enterprise. This is inseparable from the development carried out by the management. The purpose of this study was to determine the development of the Sumber Gempong Rice Field Tourism object carried out by a business entity owned by Mutiara Welirang Village. This study uses qualitative research methods with data collection techniques in the form of observation, interviews and documentation. Data analysis techniques were carried out through the stages of data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the development of tourist objects carried out by the Mutiara Welirang Village-Owned Enterprise has been carried out quite well and according to existing theory, but further improvement and development is needed on the indicators of facilities, accessibility and brand image. There needs to be more development related to the addition of facilities and means of ease of access and increased security so that tourism can adapt to current trends in order to achieve the goal of tourism development, namely to attract visitors.